Flexible and broadband colloidal quantum dots photodiode array for pixel-level X-ray to near-infrared image fusion - Liu, Jing; Liu, Peilin; Shi, Tailong; Ke, Mo; Xiong, Kao; Liu, Yuxuan; Chen, Long; Zhang, Linxiang; Liang, Xinyi; Li, Hao; Lu, Shuaicheng; Lan, Xinzheng; et al. (Nature communications, 2023)
Combining information from multispectral images into a fused image is informative and beneficial for human or machine perception. Currently, multiple photodetectors with different response bands are used, which require complicated algorithms and systems to solve the pixel and position mismatch problem. An ideal solution would be pixel-level multispectral image fusion, which involves multispectral image using the same photodetector and circumventing the mismatch problem. Here we presented the potential of pixel-level multispectral image fusion utilizing colloidal quantum dots photodiode array, with a broadband response range from X-ray to near infrared and excellent tolerance for bending and X-ray irradiation. The colloidal quantum dots photodiode array showed a specific detectivity exceeding 10 12 Jones in visible and near infrared range and a favorable volume sensitivity of approximately 2 × 10 5 μC Gy −1 cm −3 for X-ray irradiation. To showcase the advantages of pixel-level multispectral image fusion, we imaged a capsule enfolding an iron wire and soft plastic, successfully revealing internal information through an X-ray to near infrared fused image. Multispectral images suffer of pixel and position mismatch, due to the multiple sensor approach. Here, Li et al., demonstrate a flexible PbS colloidal quantum dots (CQDs) photodiode array with a broadband response range from X-ray to near infrared, enabling multi-spectral images by one single sensor.